Excavación para el muro perimetrico de la zona dos para la explanada - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1955)
SPANISH: Se observo las excavaciones para la construcción del muro perimetrico de la zona dos para la explanada del muelle a orillas del rio Amazonas.
ENGLISH: Excavations were observed for the construction of the perimeter wall of zone two for the esplanade of the dock on the banks of the Amazon River.

SPANISH: Se observo las excavaciones para la construcción del muro perimetrico de la zona dos para la explanada del muelle a orillas del rio Amazonas.
ENGLISH: Excavations were observed for the construction of the perimeter wall of zone two for the esplanade of the dock on the banks of the Amazon River.
Excavation for the perimeter wall of zone two for the esplanade
Keywords: Iquitos (Perú)|~|Urban Structure Peru|~|Wharf Construction|~|Navigation--Urban Structure|~|Iquitos (Perú)|~|Estructura Urbana|~|Perú|~|Construcción Muelle|~|Navegación|~|Estructura Urbana|~|Iquitos (Peru)|~|Urban Structure Peru|~|Wharf Construction|~|Navigation|~|Urban Structure